Neodymium-iron-boron magnet with resistivity gradient distribution structure and preparation method of neodymium-iron-boron magnet

By adding high-resistivity materials to the surface layer of the NdFeB magnet and performing hot pressing and thermal deformation treatment, a resistivity gradient distribution structure is formed, which solves the eddy current loss and thermal demagnetization problems of NdFeB magnet in a high-frequency alternating electromagnetic field environment, and the effect of reducing eddy current loss and temperature rise is achieved, and the stability and cost-effectiveness of the magnet are improved.

CN119905310APending Publication Date: 2025-04-29HEBEI UNIV OF ENG +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510114759.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the environment of high-frequency alternating electromagnetic field, the thermal demagnetization phenomenon of neodymium iron boron magnets due to eddy current loss and high working temperature, affecting the stable operation of the permanent magnet motor.

Method used

A neodymium iron boron magnet preparation method with a resistivity gradient distribution structure is adopted, and a gradient structure of a high resistivity layer and a low resistivity layer is formed by adding a high resistivity material to the surface layer of the magnet and performing hot pressing and thermal deformation.

Benefits of technology

It effectively reduces the eddy current loss and temperature rise of the magnet, improves the working stability of the magnet and the utilization rate of insulating substances, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905310A_ABST
    Figure CN119905310A_ABST
Patent Text Reader

Abstract

The invention discloses a neodymium-iron-boron magnet with a resistivity gradient distribution structure and a preparation method of the neodymium-iron-boron magnet, and the neodymium-iron-boron magnet with the resistivity gradient distribution (structure) from the surface layer to the interior is prepared by adding a high-resistivity material and concentrating the high-resistivity material on the surface layer of the magnet. According to the invention, the influence of the addition of non-magnetic substances on the overall performance of the magnet can be reduced, the high performance of the magnet is maintained, and meanwhile, the high-resistivity layer on the surface layer reduces greater eddy-current loss, so that the overall eddy-current loss of the magnet and the temperature rise of the magnet are reduced, and the working stability of the magnet and the utilization rate of an insulating substance, namely a high-resistivity material, are improved; by forming the resistivity gradient distribution structure, the addition amount of the high-resistivity material is reduced. In addition, the preparation process is simple and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of denitrification treatment, and relates to a neodymium iron boron magnet with a resistivity gradient distribution structure and a preparation method thereof. Background Art

[0002] As the third generation of rare earth permanent magnet materials, NdFeB permanent magnet materials play an important role in modern industries such as wind power generation, new energy vehicles, and electronic equipment due to their excellent magnetic properties. Among them, permanent magnet motors have become an important part of the development of the technology industry with their high efficiency, low loss, high stability, and advantages in weight and volume. However, in practical applications, the eddy current loss generated by the permanent magnets as motor rotors in the high-frequency alternating electromagnetic field environment and the high operating temperature of the motor (150℃~200℃) caused by high-speed mechanical movement often cause thermal demagnetization of NdFeB magnets with lower Curie temperature (~315℃), which seriously damages the efficient and stable operation of permanent magnet motors. Therefore, it is necessary to reduce the eddy current loss generated by permanent magnets in the high-frequency alternating electromagnetic field environment.

[0003] At present, there are two main methods to reduce the eddy current loss of magnets: one is to optimize the design of the motor rotor magnet. For example, the eddy current loss can be reduced by splitting the magnet, but splitting the magnet by a metal shell has little effect on reducing the eddy current loss and will increase the production cost; the other is to increase the resistivity of the magnet itself. The eddy current loss of the magnet is inversely proportional to the resistivity of the magnet, so increasing the resistivity of the magnet can reduce the eddy current loss.

[0004] The commonly used method to increase the resistivity of magnets is to add a certain amount of high resistivity substances such as fluorides, oxides, nitrides, etc.

[0005] For example, Chinese patent CN111243813A discloses a high resistivity ammonium iron boron rare earth alloy and its preparation method. The microstructure of the neodymium iron boron rare earth alloy is that the neodymium iron boron matrix is ​​evenly divided into different units by high resistivity insulating materials, and is composed of neodymium iron boron nanocrystalline alloy powder and a nano inorganic insulating material layer coated on its surface. This method can greatly reduce the amount of insulating material used and improve the uniformity of the distribution of the insulating material in the matrix.

[0006] Chinese patent CN104051104B discloses a NdFeB permanent magnet and a preparation method thereof, wherein the NdFeB permanent magnet comprises NdFeB magnets and rare earth compounds, wherein the rare earth compounds are uniformly distributed in the NdFeB magnets. The NdFeB permanent magnet forms a multi-layer rare earth compound barrier layer in the middle of the NdFeB magnet, which can significantly improve the magnet resistivity, and at the same time concentrate the rare earth compounds in the middle interlayer, thereby reducing the influence of the high melting point rare earth compounds on the adjacent two layers of magnet structure.

[0007] Chinese patent CN118335504 A discloses a method for preparing a NdFeB permanent magnet, specifically a method of dividing a NdFeB hot-pressed magnet and adding a nano-inorganic insulating material interlayer in the middle, thereby preparing a NdFeB permanent magnet with excellent performance and resistivity and magnetic properties that meet product usage conditions.

[0008] Chinese patent CN 101847487 A discloses a gradient resistance R-Fe-B magnet and a production method thereof. The gradient resistance R-Fe-B magnet is a sintered NdFeB magnet having at least two layers with different coercive forces, including a surface layer G and a main layer H. The surface layer G is connected to the main layer H through a sintering layer I. The oxygen content of the surface layer G is greater than that of the main layer H, and the resistivity of the surface layer G is not lower than that of the main layer H.

[0009] Chinese patent CN116666098A discloses a method for improving the resistivity of NdFeB permanent magnets in the difficult magnetization direction. By designing a mold, coating a high-resistivity material, and deforming the composite magnet, a NdFeB magnet with a higher resistivity in the direction of the difficult magnetization axis of the hot pressed / hot deformed magnet is prepared, which effectively reduces the eddy current generated in the plane perpendicular to the easy magnetization direction of the magnet.

[0010] Most of the above existing technologies improve the resistivity of the magnet by improving the insulation of magnetic powder particles or magnets. Some processes can only improve the resistivity to a limited extent and the process operations are complex, the cost is high, and more insulating materials are introduced, making it difficult to achieve stable production.

[0011] The present invention has found through electromagnetic analysis and magnetothermal analysis of permanent magnet motors that during the operation of the motor, due to the relative displacement between the NdFeB magnet rotor and the winding stator, the air gap magnetic density changes greatly in the surface area of ​​the magnet, which will lead to high induced electromotive force and higher eddy current loss. Therefore, effectively reducing the eddy current loss of the magnet surface layer is of great significance to achieving the reduction of the overall eddy current loss of the NdFeB magnet. Summary of the invention

[0012] In view of the technical problems existing in the background technology, the purpose of the present invention is to provide a neodymium iron boron magnet with a resistivity gradient distribution structure and a preparation method thereof. The method aims to reduce the eddy current loss generated by the magnet when the motor is working, so as to reduce the temperature rise of the magnet and improve the working stability of the magnet.

[0013] In order to achieve the above object, the present invention adopts the following technical solutions:

[0014] A first aspect of the present invention provides a method for preparing a NdFeB magnet having a resistivity gradient distribution structure, comprising the following steps:

[0015] S1. Preparing mixed powder: fully and evenly mixing the high resistivity material and the original NdFeB magnetic powder in a grinding dish to obtain a mixed powder;

[0016] S2, placing the original NdFeB magnetic powder and the mixed powder into a hot pressing mold in turn, and placing them into a vacuum hot pressing furnace for hot pressing molding to obtain an isotropic hot pressed NdFeB magnet;

[0017] S3. Performing thermal deformation treatment on the isotropic hot-pressed NdFeB magnet to obtain a NdFeB magnet with a resistivity gradient distribution structure.

[0018] Preferably, the components of the original NdFeB magnetic powder include, by mass percentage, Nd 10-31%, Pr 0.1-18%, Dy 0.02-5%, Co 4-5.2%, B 0.9%-1.2%, Ga 0.5-1%, and the balance is Fe.

[0019] Preferably, in step S1, the mass of the high resistivity material is 0.9-20wt% of the mixed powder.

[0020] Preferably, the high resistivity material is one of AlN, Si3N4, CaF2, NdF3, DyF3, or a combination of two or more thereof.

[0021] Preferably, in step S2, the hot pressing molding is performed in a vacuum environment, the vacuum degree is 1-10 Pa, the hot pressing molding temperature is 500-650° C., and the hot pressing molding time is 1-3 min.

[0022] Preferably, in step S3, the thermal deformation treatment is performed in an inert environment, the inert gas is argon, the thermal deformation temperature is 850-900°C, the pressure during thermal deformation is 3-5t, the pressure speed is 0.1-0.3mm / s, and the deformation amount is 70%.

[0023] The second aspect of the present invention provides a NdFeB magnet having a resistivity gradient distribution structure obtained by the above-mentioned preparation method, wherein the NdFeB magnet comprises at least two layers of NdFeB magnetic material layers with different resistivities, specifically consisting of a high resistivity layer and at least one low resistivity layer, wherein the high resistivity layer is formed by adding a high resistivity material to the original NdFeB magnetic powder, and the low resistivity layer is formed by the original NdFeB magnetic powder, i.e., without adding a high resistivity material.

[0024] Preferably, the thickness of the high resistivity layer is not higher than 50% of the total thickness of the obtained NdFeB magnet.

[0025] The present invention has the following beneficial effects:

[0026] (1) In the actual operation of the motor, the eddy current loss of the magnet gradually decreases from the surface to the inside. In view of this, the present invention prepares a NdFeB magnet with a resistivity gradient distribution (structure) from the surface to the inside by adding high-resistivity materials and concentrating them on the surface of the magnet, which can reduce the impact of the addition of non-magnetic materials on the overall performance of the magnet and maintain the high performance of the magnet. At the same time, the high-resistivity layer on the surface reduces the greater eddy current loss, thereby reducing the overall eddy current loss of the magnet and the temperature rise of the magnet, improving the working stability of the magnet and the utilization rate of the insulating material, i.e., the high-resistivity material, and reducing the production cost.

[0027] (2) In the present invention, a high resistivity (insulating) material is introduced into a hot pressed / hot deformed NdFeB magnet to obtain a NdFeB hot pressed / hot deformed magnet with high resistivity, and a resistivity gradient distribution structure is formed to reduce the amount of high resistivity (insulating) material added. In addition, the present invention has a simple preparation process and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 Schematic diagram of the structure of the gradient resistivity NdFeB magnet prepared in Example 1;

[0030] Figure 2 Schematic diagram of the structure of the gradient resistivity NdFeB magnet prepared in Example 2;

[0031] Figure 3 Schematic diagram for testing the magnetic properties and resistivity of the prepared gradient resistivity NdFeB magnet. DETAILED DESCRIPTION

[0032] In the following description, for the purpose of illustration rather than limitation, specific details such as specific system structures and technologies are provided to provide a thorough understanding of the embodiments of the present invention. However, it should be clear to those skilled in the art that the present invention may also be implemented in other embodiments without these specific details.

[0033] Example 1

[0034] S1, weigh 3g of original NdFeB magnetic powder (mainly composed of Nd 30.3 Pr 0.1 Dy 0.02 Co 4.2 B 0.92 Ga 0.51 Fe余量 ) and 0.06 g Si3N4 powder, and then the weighed original NdFeB magnetic powder and Si3N4 powder are fully and evenly mixed in an agate grinding dish to obtain a mixed powder;

[0035] S2, weigh 17g of original NdFeB magnetic powder (Nd 30.3 Pr 0.1 Dy 0.02 Co 4.2 B 0.92 Ga 0.51 Fe 余量 ), then the mixed powder and the original NdFeB magnetic powder are sequentially loaded into a hot pressing mold for hot pressing molding. The process conditions of hot pressing molding are: under vacuum environment, the temperature is raised from room temperature to 550°C within 1.5 minutes, and the temperature is kept at 550°C for 1 minute, and the pressure is 5t to obtain a hot pressed magnet;

[0036] S3. The obtained hot pressed magnet is subjected to heat deformation treatment. The process conditions of heat deformation treatment are: in an argon environment, the temperature is raised from room temperature to 850°C within 2 minutes, and then a pressure of 5t is applied for heat deformation. The heat deformation time is 1.5 minutes, the pressure speed is 0.1mm / s, the upper and lower cylinders are operated simultaneously, the deformation amount is 70%, and the size is obtained. The thermal deformation magnet is a gradient resistivity NdFeB magnet (see its structural diagram Figure 1 ).

[0037] The gradient resistivity NdFeB magnet (with a total thickness of 6.0 mm) obtained in Example 1 was cut from the center The magnetic properties of the cylinder were tested, and 5×0.9×14mm and 5×5.1×14mm cuboids were cut from the high resistivity layer B (thickness 0.95mm) and the low resistivity layer A of the magnet for resistivity measurement (see Figure 3 ). The measurement results are shown in Table 1 below.

[0038] Example 2

[0039] S1. Weigh 3g of original NdFeB magnetic powder (Nd 30.3 Pr 0.1 Dy 0.02 Co 4.2 B 0.92 Ga 0.51 Fe 余量 ) and 0.06 g Si3N4 powder, and then fully and evenly mix the two in an agate grinding dish to obtain a mixed powder;

[0040] S2, weigh 15g of original NdFeB magnetic powder (Nd 30.3 Pr 0.1 Dy 0.02 Co 4.2B 0.92 Ga 0.51 Fe 余量 ) and 2g of original NdFeB magnetic powder (Nd 30.3 Pr 0.1 Dy 0.02 Co 4.2 B 0.92 Ga 0.51 Fe 余量 ) for standby, and then sequentially fill the original NdFeB magnetic powder (15g)-mixed powder-original NdFeB magnetic powder (2g) into a hot pressing mold for hot pressing molding. The process conditions of hot pressing molding are: under vacuum environment, heating from room temperature to 550°C within 1.5min, keeping at 550°C for 1min, and the pressure is 5t to obtain a hot pressed magnet;

[0041] S3. The obtained hot pressed magnet is subjected to heat deformation treatment. The process conditions of heat deformation treatment are: in an argon environment, the temperature is raised from room temperature to 850°C within 2 minutes, and then a pressure of 5t is applied for heat deformation. The heat deformation time is 1.5 minutes, the pressure speed is 0.1mm / s, the upper and lower cylinders are operated simultaneously, the deformation amount is 70%, and the size is obtained. The thermal deformation magnet is a gradient resistivity NdFeB magnet (see its structural diagram Figure 2 ).

[0042] The center of the gradient resistivity NdFeB magnet obtained in Example 2 was cut The magnetic properties of the cylinder were tested, and 5×0.9×14mm rectangular blocks were cut from the high resistivity layer B and 5×4.5×14mm rectangular blocks were cut from the low resistivity layer A of the magnet for resistivity measurement (see Figure 3 ). The measurement results are shown in Table 1 below.

[0043] Example 3

[0044] S1. Weigh 3g of original NdFeB magnetic powder (Nd 30.3 Pr 0.1 Dy 2.1 Co 4.2 B 0.92 Ga 0.51 Fe 余量 ) and 0.06 g Si3N4 powder, and then the weighed NdFeB magnetic powder and Si3N4 powder are fully and evenly mixed in an agate grinding dish to obtain a mixed powder;

[0045] S2 weighed 15g of original NdFeB magnetic powder (Nd 30.3 Pr 0.1 Dy 2.1 Co 4.2 B 0.92 Ga 0.51 Fe 余量) and 2g of original NdFeB magnetic powder (Nd 30.3 Pr 0.1 Dy 2.1 Co 4.2 B 0.92 Ga 0.51 Fe 余量 ) for standby; then, the original NdFeB magnetic powder (15g)-mixed powder-original NdFeB magnetic powder (2g) were hot pressed in sequence, and the process conditions of hot pressing were: under vacuum environment, the temperature was raised from room temperature to 550°C within 1.5min, and kept at 550°C for 1min, and the pressure was 5t to obtain a hot pressed magnet;

[0046] S3. The obtained hot pressed magnet is subjected to heat deformation treatment. The process conditions of heat deformation treatment are: in an argon environment, the temperature is raised from room temperature to 850°C within 2 minutes, and then a pressure of 5t is applied for heat deformation. The heat deformation time is 1.5 minutes, the pressure speed is 0.15mm / s, the upper and lower cylinders are operated simultaneously, the deformation amount is 70%, and the size is obtained. The thermal deformation magnet is a gradient resistivity NdFeB magnet.

[0047] The center of the gradient resistivity NdFeB magnet obtained in Example 3 was cut The magnetic properties of the cylinder were tested, and 5×0.9×14 mm rectangular blocks were cut from the high resistivity layer B and 5×4.5×14 mm rectangular blocks were cut from the low resistivity layer A of the magnet for resistivity measurement. The measurement results are shown in Table 1 below.

[0048] Example 4

[0049] S1. Weigh 3g of original NdFeB magnetic powder (Nd 30.3 Pr 0.1 Dy 2.1 Co 4.2 B 0.92 Ga 0.51 Fe 余量 ) and 0.06 g Si3N4 powder, and then the weighed NdFeB magnetic powder and Si3N4 powder are fully and evenly mixed in an agate grinding dish to obtain a mixed powder;

[0050] S2 weighed 15g of original NdFeB magnetic powder (Nd 30.3 Pr 0.1 Dy 2.1 Co 4.2 B 0.92 Ga 0.51 Fe 余量 ) and 2g of original NdFeB magnetic powder (Nd 30.3 Pr 0.1 Dy 2.1 Co 4.2 B 0.92 Ga0.51 Fe 余量 ) for standby; then, the original NdFeB magnetic powder (15g)-mixed powder-original NdFeB magnetic powder (2g) were hot pressed in sequence, and the process conditions of hot pressing were: under vacuum environment, the temperature was raised from room temperature to 550°C within 1.5min, and kept at 550°C for 1min, and the pressure was 5t to obtain a hot pressed magnet;

[0051] S3. The obtained hot pressed magnet is subjected to heat deformation treatment. The process conditions of heat deformation treatment are: in an argon environment, the temperature is raised from room temperature to 870°C within 2 minutes, and then a pressure of 5t is applied for heat deformation. The heat deformation time is 1.5 minutes, the pressure speed is 0.15mm / s, and the upper and lower cylinders are operated simultaneously. The deformation amount is 70%, and the size is obtained. The thermal deformation magnet is a gradient resistivity NdFeB magnet.

[0052] The center of the gradient resistivity NdFeB magnet obtained in Example 4 was cut The magnetic properties of the cylinder were tested, and 5×0.9×14 mm rectangular blocks were cut from the high resistivity layer B and 5×4.5×14 mm rectangular blocks were cut from the low resistivity layer A of the magnet for resistivity measurement. The measurement results are shown in Table 1 below.

[0053] Example 5

[0054] S1. Weigh 3g of original NdFeB magnetic powder (Nd 10.9 Pr 16.9 Dy 2.1 Co 4.0 B 0.9 Ga 0.5 Fe 余量 ) and 0.6 g NdF3 powder, and then the two are fully and evenly mixed in an agate grinding dish to obtain a mixed powder;

[0055] S2, weigh 17g of original NdFeB magnetic powder (Nd 10.9 Pr 16.9 Dy 2.1 Co 4.0 B 0.9 Ga 0.5 Fe 余量 ), then the mixed powder and the original NdFeB magnetic powder are sequentially loaded into a hot pressing mold for hot pressing molding. The process conditions of hot pressing molding are: under vacuum environment, the temperature is raised from room temperature to 550°C within 1.5min, and the temperature is kept at 550°C for 1min, and the pressure is 5t to obtain a hot pressed magnet;

[0056] S3. The obtained hot pressed magnet is subjected to heat deformation treatment. The process conditions of heat deformation treatment are: in an argon environment, the temperature is raised from room temperature to 870°C within 2 minutes, and then a pressure of 5t is applied for heat deformation. The heat deformation time is 1.5 minutes, the pressure speed is 0.15mm / s, and the upper and lower cylinders are operated simultaneously. The deformation amount is 70%, and the size is obtained. The thermal deformation magnet is a gradient resistivity NdFeB magnet.

[0057] The center of the gradient resistivity NdFeB magnet obtained in Example 5 was cut The magnetic properties of the cylinder were tested, and 5×0.9×14 mm rectangular blocks were cut from the high resistivity layer B and 5×5.1×14 mm rectangular blocks were cut from the low resistivity layer A of the magnet for resistivity measurement. The measurement results are shown in Table 1 below.

[0058] Example 6

[0059] S1. Weigh 3g of original NdFeB magnetic powder (Nd 10.9 Pr 16.9 Dy 2.1 Co 4.0 B 0.9 Ga 0.5 Fe 余量 ) and 0.6 g NdF3 powder, and then the weighed NdFeB magnetic powder and NdF3 powder are fully and evenly mixed in an agate grinding dish to obtain a mixed powder;

[0060] S2, weigh 17g of original NdFeB magnetic powder (Nd 10.9 Pr 16.9 Dy 2.1 Co 4.0 B 0.9 Ga 0.5 Fe 余量 ), then the mixed powder and the original NdFeB magnetic powder are sequentially loaded into a hot pressing mold for hot pressing molding. The process conditions of hot pressing molding are: under vacuum environment, the temperature is raised from room temperature to 550°C within 1.5min, and the temperature is kept at 550°C for 1min, and the pressure is 5t to obtain a hot pressed magnet;

[0061] S3. The obtained hot pressed magnet is subjected to heat deformation treatment. The process conditions of heat deformation treatment are: in an argon environment, the temperature is raised from room temperature to 890°C within 2 minutes, and then a pressure of 5t is applied for heat deformation. The heat deformation time is 1.5 minutes, the pressure speed is 0.15mm / s, and the upper and lower cylinders are operated simultaneously. The deformation amount is 70%, and the size is obtained. The thermal deformation magnet is a gradient resistivity NdFeB magnet.

[0062] The center of the gradient resistivity NdFeB magnet obtained in Example 6 was cut The magnetic properties of the cylinder were tested, and 5×0.9×14 mm rectangular blocks were cut from the high resistivity layer B and 5×5.1×14 mm rectangular blocks were cut from the low resistivity layer A of the magnet for resistivity measurement. The measurement results are shown in Table 1 below.

[0063] Example 7

[0064] S1. Weigh 3g of original NdFeB magnetic powder (Nd 10.9 Pr 16.9 Dy 2.1 Co 4.0 B 0.9 Ga 0.5 Fe 余量 ) and 0.6 g NdF3 powder, and then the weighed NdFeB magnetic powder and NdF3 powder are fully and evenly mixed in an agate grinding dish to obtain a mixed powder;

[0065] S2, weigh 17g of original NdFeB magnetic powder (Nd 10.9 Pr 16.9 Dy 2.1 Co 4.0 B 0.9 Ga 0.5 Fe 余量 ), then the mixed powder and the original NdFeB magnetic powder are sequentially loaded into a hot pressing mold for hot pressing molding. The process conditions of hot pressing molding are: under vacuum environment, the temperature is raised from room temperature to 550°C within 1.5min, and the temperature is kept at 550°C for 1min, and the pressure is 5t to obtain a hot pressed magnet;

[0066] S3. The obtained hot pressed magnet is subjected to heat deformation treatment. The process conditions of heat deformation treatment are: in an argon environment, the temperature is raised from room temperature to 900°C within 2 minutes, and then a pressure of 5t is applied for heat deformation. The heat deformation time is 1.5 minutes, the pressure speed is 0.15mm / s, the upper and lower cylinders are operated simultaneously, the deformation amount is 70%, and the size is obtained. The thermal deformation magnet is a gradient resistivity NdFeB magnet.

[0067] The center of the gradient resistivity NdFeB magnet obtained in Example 7 was cut The magnetic properties of the cylinder were tested, and 5×0.9×14 mm rectangular blocks were cut from the high resistivity layer B and 5×5.1×14 mm rectangular blocks were cut from the low resistivity layer A of the magnet for resistivity measurement. The measurement results are shown in Table 1 below.

[0068] Comparative Example 1

[0069] S1. Weigh 3g of original NdFeB magnetic powder (Nd 30.3 Pr 0.1 Dy 0.02 Co 4.2 B 0.92Ga 0.51 Fe 余量 ) and 0.03 g Si3N4 powder, and then fully and evenly mix the two in an agate grinding dish to obtain a mixed powder;

[0070] S2, weigh 15g of original NdFeB magnetic powder (Nd 30.3 Pr 0.1 Dy 0.02 Co 4.2 B 0.92 Ga 0.51 Fe 余量 ) and 2g of original NdFeB magnetic powder (Nd 30.3 Pr 0.1 Dy 0.02 Co 4.2 B 0.92 Ga 0.51 Fe 余量 ) for standby, and then sequentially fill the original NdFeB magnetic powder (15g)-mixed powder-original NdFeB magnetic powder (2g) into a hot pressing mold for hot pressing molding. The process conditions of hot pressing molding are: under vacuum environment, heating from room temperature to 550°C within 1.5min, keeping at 550°C for 1min, and the pressure is 5t to obtain a hot pressed magnet;

[0071] S3. The obtained hot pressed magnet is subjected to heat deformation treatment. The process conditions of heat deformation treatment are: in an argon environment, the temperature is raised from room temperature to 850°C within 2 minutes, and then a pressure of 5t is applied for heat deformation. The heat deformation time is 1.5 minutes, the pressure speed is 0.1mm / s, the upper and lower cylinders are operated simultaneously, the deformation amount is 70%, and the size is obtained. The thermal deformation magnet is a gradient resistivity NdFeB magnet.

[0072] The center of the gradient resistivity NdFeB magnet prepared in Comparative Example 1 was cut The magnetic properties of the cylinder were tested, and 5×0.9×14 mm rectangular blocks were cut from the high resistivity layer B and 5×4.5×14 mm rectangular blocks were cut from the low resistivity layer A of the magnet for resistivity measurement. The measurement results are shown in Table 1 below.

[0073] Comparative Example 2

[0074] S1. Weigh 3g of original NdFeB magnetic powder (Nd 10.9 Pr 16.9 Dy 2.1 Co 4.0 B 0.9 Ga 0.5 Fe 余量 ) and 0.3 g NdF3 powder, and then the two are fully and evenly mixed in an agate grinding dish to obtain a mixed powder;

[0075] S2, weigh 17g of original NdFeB magnetic powder (Nd 10.9 Pr 16.9 Dy 2.1 Co 4.0 B 0.9 Ga 0.5 Fe 余量 ), then the mixed powder and the original NdFeB magnetic powder are sequentially loaded into a hot pressing mold for hot pressing molding. The process conditions of hot pressing molding are: under vacuum environment, the temperature is raised from room temperature to 550°C within 1.5min, and the temperature is kept at 550°C for 1min, and the pressure is 5t to obtain a hot pressed magnet;

[0076] S3. The obtained hot pressed magnet is subjected to heat deformation treatment. The process conditions of heat deformation treatment are: in an argon environment, the temperature is raised from room temperature to 870°C within 2 minutes, and then a pressure of 5t is applied for heat deformation. The heat deformation time is 1.5 minutes, the pressure speed is 0.15mm / s, and the upper and lower cylinders are operated simultaneously. The deformation amount is 70%, and the size is obtained. The thermal deformation magnet is a gradient resistivity NdFeB magnet.

[0077] The center of the gradient resistivity NdFeB magnet prepared in Comparative Example 2 was cut The magnetic properties of the cylinder were tested, and 5×0.9×14 mm rectangular blocks were cut from the high resistivity layer B and 5×5.1×14 mm rectangular blocks were cut from the low resistivity layer A of the magnet for resistivity measurement. The measurement results are shown in Table 1 below.

[0078] Table 1. Magnetic properties and resistivity test results of magnets

[0079]

[0080]

[0081] As can be seen from the results in Table 1, by comparing the test results of Examples 1 and 2, using Si3N4 powder as a high resistivity material can improve the magnetic properties of the obtained magnet while maintaining the high resistivity of the magnet, thereby adapting to the application of the magnet in permanent magnet motors. In addition, since the addition of nano-Si3N4 powder affects the formability of the magnet during the thermal deformation of the magnet, by optimizing the distribution structure of the high resistivity layer, the structural stability of the prepared magnet can be further improved by separately adding the original NdFeB magnetic powder without affecting the overall gradient resistivity distribution structure of the magnet.

[0082] Comparing the test results of Examples 2-4, on the basis of Example 2, NdFeB magnetic powder with added heavy rare earth Dy is used as the matrix. By optimizing the deformation process such as deformation temperature, deformation rate, etc., the magnetic properties of the magnet can be further improved while maintaining a high resistivity gradient distribution structure, thereby meeting the application of NdFeB magnets in motors.

[0083] Comparing the test results of Examples 5-7, it is possible to prepare a magnet with high magnetic properties and resistivity gradient distribution structure by using NdF3 powder as the high resistivity material and NdFeB magnetic powder added with heavy rare earth Dy as the matrix through optimizing the deformation process.

[0084] Comparing Example 2 with Comparative Example 1, and Example 5 with Comparative Example 2, under the same process and gradient structure, the higher the content of high-resistivity material in the high-resistivity layer, the higher the resistivity, but the worse the magnetic properties of the magnet.

[0085] The present invention is not limited to the above-mentioned specific implementation modes. Various changes made by ordinary technicians in this field based on the above-mentioned concepts without creative work are all within the protection scope of the present invention.

Claims

1. A method for preparing a neodymium iron boron magnet having a resistivity gradient distribution structure, characterized in that: The following steps are involved: S1. Preparing mixed powder: fully and evenly mixing the high resistivity material and the original NdFeB magnetic powder in a grinding dish to obtain a mixed powder; S2, placing the original NdFeB magnetic powder and the mixed powder into a hot pressing mold in turn, and placing them into a vacuum hot pressing furnace for hot pressing molding to obtain an isotropic hot pressed NdFeB magnet; S3. Performing thermal deformation treatment on the isotropic hot-pressed NdFeB magnet to obtain a NdFeB magnet with a resistivity gradient distribution structure.

2. The method for preparing a NdFeB magnet having a resistivity gradient distribution structure according to claim 1, characterized in that: The components of the original NdFeB magnetic powder include, by mass percentage, Nd 10-31%, Pr 0.1-18%, Dy 0.02-5%, Co 4-5.2%, B 0.9-1.2%, Ga 0.5-1%, and the balance Fe.

3. The method for preparing a NdFeB magnet having a resistivity gradient distribution structure according to claim 1, characterized in that: In step S1, the mass of the high resistivity material is 0.9-20wt% of the mixed powder.

4. The method for preparing a NdFeB magnet having a resistivity gradient distribution structure according to claim 1, characterized in that: The high resistivity material is one of AlN, Si3N4, CaF2, NdF3, and DyF3, or a combination of two or more thereof.

5. The method for preparing a NdFeB magnet having a resistivity gradient distribution structure according to claim 1, characterized in that: In step S2, the hot pressing molding is performed in a vacuum environment, the vacuum degree is 1-10 Pa, the hot pressing molding temperature is 500-650° C., the hot pressing molding pressure is 3-5t, and the hot pressing molding time is 1-3 min.

6. The method for preparing a NdFeB magnet having a resistivity gradient distribution structure according to claim 1, characterized in that: In step S3, the thermal deformation treatment is performed in an inert environment, the inert gas is argon, the thermal deformation temperature is 850-900°C, the pressure during thermal deformation is 3-5t, the pressure speed is 0.1-0.3mm / s, and the deformation amount is 70%.

7. A NdFeB magnet having a resistivity gradient distribution structure obtained by the preparation method according to any one of claims 1 to 6.

8. The NdFeB magnet according to claim 7, characterized in that: The NdFeB magnet consists of a high resistivity layer and a low resistivity layer, wherein the thickness of the high resistivity layer is not higher than 50% of the total thickness of the obtained NdFeB magnet.

Citation Information

Patent Citations

  • Gradient coercive-force neodymium-ferrum-boron magnet and production method thereof

    CN101847487A

  • NdFeB permanent magnet and preparation method thereof

    CN104051104B

  • High-resistivity neodymium-iron-boron permanent magnet alloy and preparation method thereof

    CN111243813A

  • Method for improving resistivity of neodymium iron boron permanent magnet in difficult magnetization direction

    CN116666098A

  • NdFeB permanent magnet and preparation method thereof

    CN104051104A